Relationships between kinematic characteristics and ratio of forces during initial sprint acceleration - DANIEL KING (2022)
In track sprinting, the athlete generates around 70% of their maximum velocity during the initial acceleration phase (Nagahara et al., 2019a). Effective acceleration performance is largely determined by the technical ability of effectively orientating force applied to the track, quantified by the ratio of forces (RF; Morin et al., 2011). This thesis aimed to investigate the relationships between kinematic characteristics and RF during the initial acceleration phase of sprinting, as these important considerations remain unknown. Fourteen male sprinters completed two maximal 60 m sprint efforts from a block start. Whole-body kinematic data and external kinetic data were measured for the first four steps on the track. An initial analysis using semi-partial correlations (sr) determined that step-to-step variation in RF over the four steps was not related (sr = -0.280) to initial acceleration performance (normalised average horizontal external power; NAHEP), but that mean RF (RFMEAN) over these steps was strongly related to initial acceleration performance (sr = 0.683). To address the aim of this thesis, correlations with kinematic characteristics, using RFMEAN as the dependent variable, revealed that placing the stance foot further behind the whole-body centre of mass at touchdown was strongly related to high RF (r = -0.672). Specific stance leg configurations contributed to this favourable touchdown distance - a more anterior orientation (i.e., of the proximal end) of the foot and shank segments were both very strongly associated with RF (r = -0.724 and r = -0.764, respectively). Following touchdown, ankle dorsiflexion range of motion was also very strongly related to RF (r = 0.728). Touchdown distance was the only measure strongly related to both RF and performance (r = -0.710 with NAHEP). These findings suggest coaches should focus on strategies which manipulate lower-leg configurations at touchdown and actions during early stance if they wish to improve RF ability.